Less [large type] : a novel - Greer, Andrew Sean (Little, Brown and Company, 2018)
Who says you can't run away from your problems? You are a failed novelist about to turn fifty. A wedding invitation arrives in the mail: your boyfriend of the past nine years is engaged to someone else. You can't say yes--it would be too awkward--and you can't say no--it would look like defeat. On your desk are a series of invitations to half-baked literary events around the world. QUESTION: How do you arrange to skip town? ANSWER: You accept them all. What would possibly go wrong? Arthur Less will almost fall in love in Paris, almost fall to his death in Berlin, barely escape to a Moroccan ski chalet from a Saharan sandstorm, accidentally book himself as the (only) writer-in-residence at a Christian Retreat Center in Southern India, and encounter, on a desert island in the Arabian Sea, the last person on Earth he wants to face. Somewhere in there: he will turn fifty. Through it all, there is his first love. And there is his last.